METHODOLOGICAL APPROACHES TO ACCOUNTING AND ANALYTICAL SUPPORT FOR INTANGIBLE ASSET MANAGEMENT - Plekan, Mariia (Social Development: Economic and Legal Issues, 2026)
The purpose of the study is to develop a comprehensive methodological approach to the accounting and analytical support of intangible asset management. The proposed solution integrates accounting, analytical evaluation, digital integration, and internal audit into a single functional system. Instead of using isolated accounting tools, the study focuses on a coordinated architecture that transforms fragmented information on software, patents, trademarks, licenses, databases, and digital products into a structured information base for managerial decision-making. The methodological framework is based on a systems approach, structural and functional analysis, methods of classification, modeling, integral assessment, and tabular design. The source base includes current regulatory and legal acts, methodological recommendations on accounting, works of domestic and foreign scholars, as well as modern practices of digital accounting for intellectual capital. The article substantiates an algorithm for the multicriteria recognition of intangible assets, improves the approach to determining their initial cost, proposes an adaptive depreciation mechanism, and develops a system of integral indicators for assessing the condition, informational relevance, and economic efficiency of their use. An architecture of the digital environment has been formed, consolidating ERP modules, intellectual property rights registers, analytical platforms, audit trail logs, and automated control procedures. The obtained results have practical significance for enterprises operating in various industries. The developed toolkit contributes to improving the reliability of accounting data, minimizing the risk of financial statement misstatements, strengthening control over intellectual resources, and supporting well-grounded strategic decisions regarding their commercialization. The scientific novelty lies in the integration of accounting, analytical, and control procedures within a unified model of intangible asset management adapted to the digital environment, which ensures the transition from fragmented accounting to systematic information support of managerial processes.